CONTENT CURATION IN NETWORK EDUCATIONAL EVENTS - Vyacheslav A. Starodubtsev; Olga B. Shamina (Высшее образование в России)
The article discusses the need to embed now the content curators into educational events of different levels. Content curator fulfills important didactic functions such as analytic and research, as well as compensatory, reducing overhead and forces other users to find relevant information. Personal knowledge management is considered as a basis of the content curation. This role can be performed by a teacher or a student including in the context of the massive open online courses (or MOOCs). In general, content curation increases the subjectivity and personality of education space.